Upaya Guru Dalam Meningkatkan Hasil Belajar Matematika Melalui Permainan Kartu Pecahan Pada Siswa Sekolah Dasar Islam Terpadu Al-Hasna - Herawati, Hana; Arkiang, Fajeri (putrapublisher.org, 2023)
The aim of this research is to determine the increase in mathematics learning outcomes regarding simple fractions through fraction card games. This research is a PTK type research with 4 stages, namely: (1) scheduling research, (2) carrying out learning improvement activities, (3) observing and (4) reflecting. This PTK analysis method is qualitative quantitative descriptive analysis. Qualitative data is reviewed at the reflection stage according to the findings in class when observing learning activities. Meanwhile, quantitative data is analyzed from student learning outcomes. The research will be stopped if the learning outcomes reach KKM ≥73. The subjects in this study were 24 people consisting of 13 male students and 11 female students. The results obtained in the learning improvement stage increased with the class average score from 70 changing to 95, with a difference of 25% increase. The research results prove that using fraction cards can improve students' understanding of simple fraction material.